Polyethylene copolymer and terpolymer hot melt adhesive compositions, articles, and methods for preparing same
Patent Information
- Application Number
- JP2023543183
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-01-19
- Filing Date
- 2022-01-19
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2042-01-19
AI Technical Summary
Existing hot melt adhesives face challenges in achieving optimal bond strength and thermal stability across a wide range of applications, particularly when bonding diverse substrates, due to variations in molecular weight, branching, and comonomer distribution.
Development of hot melt adhesive compositions comprising ethylene, branched vinyl ester monomers, and tackifiers, with optional additives like antioxidants and waxes, formulated to enhance molecular weight distribution and thermal properties.
The compositions exhibit improved bond strength, thermal stability, and reduced viscosity, making them suitable for a broader range of substrates and applications, including textiles, nonwovens, and polymeric materials.
Smart Images

Figure 2022157585000001 
Figure 2022157585000002
Abstract
Description
[Technical field]
[0001] The present invention relates to hot melt adhesive compositions, articles, and methods for preparing same. [Background technology]
[0002] The production of polyolefin materials, such as polyethylene (PE) and polypropylene (PP), is the largest volume of synthetic polymers ever invented. The success of these materials has been largely achieved due to low production costs, energy efficiency, low greenhouse gas emissions, versatility to produce a wide range of polymers with different properties, and high polymer processability. A wide range of articles are manufactured using polyolefin materials, including films, molded articles, foams, pipes, textiles, and more. The increasing complexity of manufactured articles has led to major improvements and developments, especially in the hot melt adhesive industry. Hot melt adhesives are used in a wider range of adhesive application process windows, with a larger end-use portfolio, to bond to a wider variety of substrates. During application, hot melt adhesives are applied in a molten state and cooled to harden the adhesive bond. Furthermore, adhesives must meet a number of requirements once set, which may include bond strength, bond retention under or after mechanical stress, or adequate bond retention under or after various thermal conditions.
[0003] The physical and chemical properties of hot melt adhesives may respond differently depending on several factors, such as molecular weight, molecular weight distribution, content, nature and distribution of comonomer(s), presence and distribution of short and / or long chain branching, thermal and shear history, etc., that define their applicability in a particular application. To increase the utility of hot melt adhesives, they can include multiple polymers and can be formulated as random and block copolymers with many possible comonomers, and can also include many potential additives. Summary of the Invention [Means for solving the problem]
[0004] This Summary is provided to introduce some concepts that are further described below in the Detailed Description. This Summary is not intended to identify key or essential features of the claimed subject matter, nor is it intended to be used as an aid in limiting the claimed subject matter. In one aspect, embodiments disclosed herein relate to a hot melt adhesive composition comprising a polymer formed from ethylene, one or more branched vinyl ester monomers, and optionally vinyl acetate, and a tackifier.
[0005] In another aspect, embodiments disclosed herein relate to a method of making a hot melt adhesive composition comprising adding a polymer formed from ethylene, one or more branched vinyl ester monomers, and optionally vinyl acetate, and a tackifier to a mixer; adding an optional wax and / or antioxidant to the mixer; and mixing the polymer and tackifier, and the optional wax and / or antioxidant at a temperature ranging from 150° C. to 200° C. to form the hot melt adhesive composition.
[0006] In yet another aspect, embodiments disclosed herein relate to the use of the hot melt adhesive composition for bonding a substrate selected from the group consisting of textiles, nonwoven materials, polyurethanes, ethylene vinyl acetate copolymers, polypropylene, polyethylene, polyvinyl chloride, polyesters, polyamides, wood, metals, paper, and kraft paper to similar or dissimilar substrates.
[0007] In another aspect, embodiments disclosed herein relate to a method of bonding a substrate to a similar or dissimilar substrate, the method comprising applying a hot melt adhesive composition to at least one substrate and bonding the substrate and the hot melt adhesive composition together.
[0008] In another aspect, embodiments disclosed herein relate to a multi-layer article comprising at least one layer of the hot melt adhesive composition and one or more substrate layers.
[0009] Other aspects and advantages of the claimed subject matter will become apparent from the following description and the appended claims. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] In one aspect, the disclosed embodiments relate to a hot melt adhesive composition comprising a polymer formed from ethylene, one or more branched vinyl ester monomers, and optionally vinyl acetate, and a tackifier. In one or more embodiments, the hot melt adhesive composition may optionally include secondary polymers, waxes, antioxidants, plasticizers, UV stabilizers, pigments and dyes, glitters, biocides, flame retardants, antistatic agents, and fillers.
[0011] In one or more embodiments, the polymer may be prepared by the reaction of ethylene with one or more branched vinyl esters, optionally including vinyl acetate, that modify various properties of the copolymer formed, including molecular weight, molecular weight distribution, crystallinity, hardness, melting temperature, glass transition temperature, among others.
[0012] In one or more embodiments, the hot melt adhesive composition has a number average molecular weight (M) in the range of 5 to 10,000 kDa, as determined by GPC. n ), and a polymer having a molecular weight distribution in the range of 1-60.
[0013] The hot melt adhesive composition according to the present disclosure may include a polymer that is a copolymer incorporating ethylene and one or more branched vinyl esters in various ratios. In one or more embodiments, the polymer may be prepared by reacting ethylene with a branched vinyl ester in the presence of an additional comonomer and one or more radical initiators to form a copolymer. In other embodiments, the hot melt adhesive composition may include a polymer that is a terpolymer. The terpolymer may be prepared by reacting ethylene with a first comonomer to form a polymer resin or prepolymer, which is then reacted with a second comonomer to prepare the final polymer composition, where the first and second comonomers can be added in the same reactor or in different reactors. In one or more embodiments, the terpolymer may be composed of ethylene, one or more branched vinyl esters, and vinyl acetate. In one or more embodiments, the copolymer may be prepared by reacting ethylene with one or more comonomers in one or more polymerization reaction stages to obtain various repeat unit microstructures.
[0014] Branched Vinyl Ester Monomer In one or more embodiments, the branched vinyl ester may include a branched vinyl ester produced from an isomeric mixture of branched alkyl acids. The branched vinyl ester according to the present disclosure has the general structure (I):
[0015] [ka]
[0016] (In the formula, R 1 , R 2 , and R 3 has a total carbon number ranging from C3 to C20) In one or more embodiments, R 1 , R 2 , and R 3 may each be an alkyl chain with various degrees of branching in one or more embodiments, or R1 , R 2 , and R 3 may be independently selected from the group consisting of hydrogen, alkyl, or aryl in one or more embodiments.
[0017] In one or more embodiments, the branched vinyl ester monomer has the general structure (II):
[0018] [ka]
[0019] (In the formula, R 4 and R 5 has a total of 6 or 7 carbon atoms and the polymer composition has a number average molecular weight (Mn) in the range of 5 kDa to 10,000 kDa as determined by GPC. 4 and R 5 may have a total carbon number of less than 6 or more than 7, and the polymer composition has a M of 10,000 kDa or less. n That is, M n If is less than 5 kDa, R 4 and R 5 may have a total carbon number less than 6 or more than 7, but M n If R exceeds 5 kDa, for example, in the range of 5 to 10,000 kDa, 4 and R 5 can contain a total of 6 or 7 carbon atoms. In certain embodiments, R 4 and R 5 has a total of 7 carbon atoms, M n may be in the range of 5 to 10000 kDa. Furthermore, in one or more specific embodiments, a vinyl ester according to formula (II) may be used in combination with vinyl acetate.
[0020] Examples of branched vinyl esters include those having the following chemical structure:
[0021] [ka]
[0022] Examples of the monomer include monomers having the formula:
[0023] In one or more embodiments, the hot melt adhesive composition may comprise a polymer having a branched vinyl ester content ranging from a lower limit selected from one of 0.01 wt%, 0.1 wt%, 1 wt%, 5 wt%, 10 wt%, 20 wt%, or 30 wt%, to an upper limit selected from 50 wt%, 60 wt%, 70 wt%, 80 wt%, 89.99 wt%, or 90 wt%, any lower limit may be combined with any upper limit.
[0024] In one or more embodiments, the branched vinyl ester may comprise a mixture of monomers and comonomers, including vinyl esters such as neononanoic acid, neodecanoic acid, etc. In one or more embodiments, the branched vinyl ester may comprise tertiary carboxylic acids from the Versatic™ acid series, including Versatic™ acid EH, Versatic™ acid 9, and Versatic™ acid 10, prepared by Koch synthesis and commercially available from Hexion™ chemicals, Inc. In one or more embodiments, the hot melt adhesive composition may comprise a polymer produced from monomers derived from petroleum and / or renewable resources.
[0025] The hot melt adhesive composition according to the present disclosure is characterized by the proton nuclear magnetic resonance ( 1 H NMR) and carbon-13 nuclear magnetic resonance ( 13The branched vinyl ester-containing polymer may have a weight percent ethylene, as measured by C NMR, ranging from a lower limit selected from one of 10 wt%, 20 wt%, or 30 wt% to an upper limit selected from one of 60 wt%, 70 wt%, 80 wt%, 90 wt%, 95 wt%, 99.9 wt%, and 99.99 wt%, any lower limit may be combined with any upper limit.
[0026] The hot melt adhesive composition according to the present disclosure comprises 1 H NMR and 13 The branched vinyl ester-containing polymer may comprise a weight percent of vinyl ester monomer, such as those of formulas (I) and (II) above, as measured by C NMR ranging from a lower limit selected from one of 0.01 wt%, 0.1 wt%, 1 wt%, 5 wt%, 10 wt%, 20 wt%, or 30 wt%, to an upper limit selected from 50 wt%, 60 wt%, 70 wt%, 80 wt%, 89.99 wt%, or 90 wt%, any lower limit may be combined with any upper limit.
[0027] In one or more embodiments, the hot melt adhesive composition according to the present disclosure optionally comprises a range of from a lower limit selected from one of 0 wt%, 0.01 wt%, 0.1 wt%, 1 wt%, 5 wt%, 10 wt%, 20 wt%, or 30 wt%, to an upper limit selected from 50 wt%, 60 wt%, 70 wt%, 80 wt%, or 89.99 wt%. 1 H NMR and 13 The branched vinyl ester-containing polymer may have a weight percent vinyl acetate as measured by C NMR, and any lower limit may be combined with any upper limit.
[0028] The hot melt adhesive composition according to the present disclosure has a number average molecular weight (M) in kilodaltons (kDa) ranging from a lower limit selected from one of 1 kDa, 5 kDa, 10 kDa, 15 kDa, and 20 kDa to an upper limit selected from one of 40 kDa, 50 kDa, 100 kDa, 300 kDa, 500 kDa, 1000 kDa, 5000 kDa, and 10000 kDa, as measured by gel permeation chromatography (GPC). n ), and any lower limit may be combined with any upper limit.
[0029] The hot melt adhesive composition according to the present disclosure may comprise a branched vinyl ester-containing polymer having a molecular weight distribution (MWD, defined as the ratio of Mw to Mn) as measured by GPC, with a lower limit of either 1, 2, 5 or 10 and an upper limit of either 20, 30, 40, 50 or 60, any lower limit may be combined with any upper limit.
[0030] The hot melt adhesive composition according to the present disclosure has a weight average molecular weight (M) in kilodaltons (kDa) ranging from a lower limit selected from one of 1 kDa, 5 kDa, 10 kDa, 15 kDa, and 20 kDa to an upper limit selected from one of 40 kDa, 50 kDa, 100 kDa, 200 kDa, 300 kDa, 500 kDa, 1000 kDa, 2000 kDa, 5000 kDa, 10000 kDa, and 20000 kDa, as measured by GPC. w ), and any lower limit may be combined with any upper limit.
[0031] In one or more embodiments, the hot melt adhesive composition may comprise an amount of branched vinyl ester-containing polymer ranging from a lower limit selected from one of 10 wt%, 15 wt%, 20 wt%, and 30 wt% to an upper limit selected from one of 40 wt%, 50 wt%, 60 wt% 70 wt%, 80 wt%, and 90 wt% of the hot melt adhesive composition, any lower limit may be combined with any upper limit.
[0032] Secondary Polymer In one or more embodiments, the hot melt adhesive composition according to the present disclosure may further comprise a secondary polymer selected from the group consisting of ethylene vinyl acetate copolymer (EVA), ethylene-acrylic ester copolymers such as ethylene butyl acrylate copolymer (EBA), ethylene-methyl acrylate copolymer (EMA), polyethylene, polypropylene, styrene block copolymers (e.g., SBS, SIS, SEBS, SEPS), and combinations thereof.
[0033] The secondary polymer according to the present disclosure may have a melt index ranging from a lower limit selected from any of 0.1 g / 10 min, 1 g / 10 min, 2 g / 10 min, 2.5 g / 10 min, 25 g / 10 min, 100 g / 10 min, 150 g / 10 min, and 200 g / 10 min, to an upper limit selected from any of 250 g / 10 min, 300 g / 10 min, 400 g / 10 min, 500 g / 10 min, and 1000 g / 10 min, any lower limit may be combined with any upper limit, as determined by ASTM D1238 at 190° C. using a load of 2.16 kg.
[0034] In one or more embodiments, the hot melt adhesive composition may comprise an amount of the secondary polymer ranging from a lower limit selected from one of 0.1 wt%, 1 wt%, 2 wt%, 5 wt%, 7 wt%, 10 wt%, 15 wt%, and 20 wt% to an upper limit selected from one of 25 wt%, 30 wt%, 40 wt%, 45 wt%, 50 wt%, 60 wt%, 70 wt%, 80 wt%, and 90 wt% of the hot melt adhesive composition, any lower limit may be combined with any upper limit.
[0035] Tackifier The tackifier according to the present disclosure may be a chemical or low molecular weight polymer that enhances the adhesion of the hot melt adhesive composition. The tackifier may include any compatible resin or mixture thereof, such as natural and modified rosins, including gum rosin, wood rosin, tall oil rosin, distilled rosin, hydrogenated rosin, dimerized rosin, rosin esters and polymerized rosins; glycerin and pentaerythritol esters of natural and modified rosins, including phenolic modified rosins and rosin esters; monomeric resins; polymers and copolymers of natural terpenes such as pinene; terpene resins; hydrogenated polyterpene resins; phenolic modified terpene resins and hydrogenated derivatives thereof; indene-coumarone resins; aliphatic petroleum hydrocarbon resins; hydrogenated aliphatic petroleum hydrocarbon resins; C5 / C9 hydrocarbon resins, including cyclic or acyclic C5 resins and aromatic modified acyclic or cyclic resins, cyclic petroleum hydrocarbon resins and hydrogenated derivatives thereof, and the like. In one or more embodiments, the tackifier may be selected from hydrocarbon resins. In other embodiments, the tackifier may be selected from hydrocarbon resins marketed by Braskem, such as resins from the UNILENE® family including Unilene A80, Unilene A90, Unilene A100 or Unilene A120.
[0036] In one or more embodiments, the hot melt adhesive composition may include an amount of tackifier ranging from a lower limit selected from one of 10 wt%, 15 wt%, 20 wt%, 25 wt%, 30 wt%, and 40 wt% to an upper limit selected from one of 60 wt%, 70 wt%, 80 wt%, and 90 wt% of the hot melt adhesive composition, any lower limit may be combined with any upper limit.
[0037] In one or more embodiments, the tackifier may be formulated as a concentrate or a "tackifier masterbatch" in combination with other polymers and / or additives to prepare the hot melt composition. The tackifier masterbatch may be prepared in any conventional resin mixing process, such as a solubilization process and an extrusion process. In one or more embodiments, the tackifier masterbatch may be formulated with the tackifier and any suitable base polymer that has good compatibility with other components of the hot melt adhesive composition. In a particular embodiment, the base polymer is an EVA copolymer.
[0038] A tackifier masterbatch according to the present disclosure may include a tackifier in a weight percent (wt%) ranging from 20 wt% to 70 wt% of the masterbatch and a base polymer in a weight percent (wt%) ranging from 20 wt% to 70 wt% of the masterbatch.
[0039] In one or more embodiments, the hot melt adhesive composition may be combined with a tackifier masterbatch in a weight percent (wt%) range of 20 wt% to 70 wt% of the adhesive composition.
[0040] wax The hot melt adhesive composition according to the present disclosure may optionally incorporate one or more waxes. Waxes suitable for use in the present invention include paraffin wax, microcrystalline wax, high density low molecular weight polyethylene wax, by-product polyethylene wax, Fischer-Tropsch wax, oxidized Fischer-Tropsch wax, and functionalized waxes such as hydroxystearamide wax and fatty acid amide wax. It is common in the industry to use the term synthetic high melting point wax to include high density low molecular weight polyethylene wax, by-product polyethylene wax, and Fischer-Tropsch wax. Modified waxes such as vinyl acetate modified wax and maleic anhydride modified wax may also be used. Exemplary waxes useful in the practice of the present invention have a melting point of about 64°C to about 600°C and an oil content of less than about 0.5.
[0041] Specific examples include paraffin waxes having a Ring and Ball softening point of about 55° C. to about 85° C. Exemplary paraffin waxes are Okerin® 236 TP available from Astor Wax Corporation, Doraville, Ga.; Penreco® 4913 available from Pennzoil Products Co., Houston, Tex.; R-7152 Paraffin Wax available from Moore & Munger, Shelton, CN.; and Paraffin Wax 1297 available from International Waxes, Ltd, Ontario, Canada. Particularly preferred are paraffin waxes having melting points in the range of about 130-165° F., such as Pacemaker available from Citgo, and R-2540 available from Moore and Munger; and low melting synthetic Fischer-Tropsch waxes having melting points below about 180° F., including the Escorez series available from ExxonMobil Chemical Company, Houston, Texas. The most preferred wax is paraffin wax having a melting point of 150° F. Other paraffin waxes include those available from CP Hall under the product designations 1230, 1236, 1240, 1245, 1246, 1255, 1260 and 1262. CP Hall 1246 paraffin wax is available from CP Hall, Stow, Ohio.
[0042] In one or more embodiments, the hot melt adhesive composition may include an amount of wax ranging from a lower limit selected from one of 0.1 wt%, 0.5 wt%, 1 wt%, and 5 wt% to an upper limit selected from one of 15 wt%, 20 wt%, 25 wt%, 30 wt%, 35 wt%, and 40 wt% of the hot melt adhesive composition, any lower limit may be combined with any upper limit.
[0043] Antioxidants The hot melt adhesive composition according to the present disclosure may optionally incorporate one or more antioxidants. Antioxidants suitable for use in the present invention may include 4,4'-methylenebis(2,6-di-tert-butylphenol), 2,2'-methylenebis(4-methyl-6-tert-butylphenol), pentaerythritol tetrakis[3,(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], di-stearyl-3,3'-thiodipropionic acid (DSTDP), phosphites including tris-(p-nonylphenyl)-phosphite (TNPP), and bis(2,4-di-tert-butylphenyl)4,4'-diphenylene-diphosphonite. Antioxidants suitable for use in the present invention are commercially available under a variety of product names, including the IRGANOX series, available from BASF Corporation, Florham Park, N.J. under the product names IRGANOX 1010, IRGANOX 565, IRGANOX 1076 and IRGAFOS 168.
[0044] In one or more embodiments, the hot melt adhesive composition may include an amount of antioxidant ranging from a lower limit selected from one of 0.01 wt%, 0.02 wt%, 0.03 wt%, 0.04 wt%, and 0.05 wt% to an upper limit selected from one of 0.1 wt%, 0.2 wt%, 0.3 wt%, 0.4 wt%, 0.5 wt%, 1 wt%, 2 wt%, 3 wt%, 4 wt%, and 5 wt% of the hot melt adhesive composition, any lower limit may be combined with any upper limit.
[0045] Initiators for free radical polymerization The hot melt adhesive composition according to the present disclosure may include polymers synthesized with one or more initiators for radical polymerization capable of generating free radicals that initiate chain polymerization of comonomers and prepolymers in the reactant mixture. In one or more embodiments, the radical initiator may include chemical species that decompose spontaneously or under stimulation by temperature, pH, or other trigger to release free radicals.
[0046] In one or more embodiments, the radical initiators include peroxides and difunctional peroxides, such as benzoyl peroxide; dicumyl peroxide; di-tert-butyl peroxide; tert-butyl cumyl peroxide; t-butyl peroxy-2-ethyl-hexanoate; tert-butyl peroxypivalate; tertiary butyl peroxyneodecanoate; t-butyl peroxy-benzoate; t-butyl peroxy-2-ethyl-hexanoate; tert-butyl 3,5,5-trimethylhexanoate peroxide; tert-butyl peroxybenzoate; 2-ethylhexyl carbamide. butyl 4,4-di(tert-butylperoxide)valerate; di(2,4-dichlorobenzoyl)peroxide; di(4-methylbenzoyl)peroxide; di(tert-butylperoxyisopropyl)benzene peroxide, and the like.
[0047] Radical initiators include benzoyl peroxide, 2,5-di(cumylperoxy)-2,5-dimethylhexane, 2,5-di(cumylperoxy)-2,5-dimethylhexyne-3,4-methyl-4-(t-butylperoxy)-2-pentanol, 4-methyl-4-(t-amylperoxy)-2-pentanol, 4-methyl-4-(cumylperoxy)-2-pentanol, 4-methyl-4-(t-butylperoxy)-2-pentanone, 4-methyl-4-(t-amylperoxy)-2-pentanone, 4-Methyl-4-(cumylperoxy)-2-pentanone, 2,5-dimethyl-2,5-di(t-butylperoxy)hexane, 2,5-dimethyl-2,5-di(t-amylperoxy)hexane, 2,5-dimethyl-2,5-di(t-butylperoxy)hexyne-3, 2,5-dimethyl-2,5-di(t-amylperoxy)hexyne-3, 2,5-dimethyl-2-t-butylperoxy-5-hydroperoxyhexane, 2,5-dimethyl-2-cumylperoxy-5-hydroperoxyhexane, 2, 5-Dimethyl-2-t-amylperoxy-5-hydroperoxyhexane, m / p-alpha, alpha-di[(t-butylperoxy)isopropyl]benzene, 1,3,5-tris(t-butylperoxyisopropyl)benzene, 1,3,5-tris(t-amylperoxyisopropyl)benzene, 1,3,5-tris(cumylperoxyisopropyl)benzene, di[1,3-dimethyl-3-(t-butylperoxy)butyl]carbonate, di[1,3-dimethyl-3-(t-amylperoxy )butyl]carbonate, di[1,3-dimethyl-3-(cumylperoxy)butyl]carbonate, di-t-amyl peroxide, t-amyl cumyl peroxide, t-butyl-isopropenyl cumyl peroxide, 2,4,6-tri(butylperoxy)-s-triazine, 1,3,5-tri[1-(t-butylperoxy)-1-methylethyl]benzene, 1,3,5-tri-[(t-butylperoxy)-isopropyl]benzene, 1,3-dimethyl-3-(t-butylperoxy)butanol, 1,3-Dimethyl-3-(t-amylperoxy)butanol, di(2-phenoxyethyl)peroxydicarbonate, di(4-t-butylcyclohexyl)peroxydicarbonate, dimyristylperoxydicarbonate, dibenzylperoxydicarbonate, di(isobornyl)peroxydicarbonate, 3-cumylperoxy-1,3-dimethylbutylmethacrylate, 3-t-butylperoxy-1,3-dimethylbutylmethacrylate, 3-t-amylperoxy-1,3-dimethylbutylmethacrylate ester, tri(1,3-dimethyl-3-t-butylperoxybutyloxy)vinylsilane, 1,3-dimethyl-3-(t-butylperoxy)butyl N-[1-{3-(1-methylethenyl)-phenyl)1-methylethyl]carbamate, 1,3-dimethyl-3-(t-amylperoxy)butyl N-[1-{3(1-methylethenyl)-phenyl}-1-methylethyl]carbamate, 1,3-dimethyl-3-(cumylperoxy))butyl N-[1-{3-(1-methylethenyl)-phenyl}-1-methylethyl]carbamate ethyl]carbamate, 1,1-di(t-butylperoxy)-3,3,5-trimethylcyclohexane, 1,1-di(t-butylperoxy)cyclohexane, n-butyl 4,4-di(t-amylperoxy)valerate, ethyl 3,3-di(t-butylperoxy)butyrate, 2,2-di(t-amylperoxy)propane, 3,6,6,9,9-pentamethyl-3-ethoxycarbonylmethyl-1,2,4,5-tetraoxacyclononane, n-butyl-4,4-bis(t-butylperoxy)valerate, ethyl ethyl-3,3-di(t-amylperoxy)butyrate, benzoyl peroxide, OO-t-butyl-O-hydrogen-monoperoxy-succinate, OO-t-amyl-O-hydrogen-monoperoxy-succinate, 3,6,9,triethyl-3,6,9-trimethyl-1,4,7-triperoxynonane (or methyl ethyl ketone peroxide cyclic trimer), methyl ethyl ketone peroxide cyclic dimer, 3,3,6,6,9,9-hexamethyl-1,2,4,5-tetraoxacyclononane, 2,5-dimethyl-2,5-Di(benzoylperoxy)hexane, t-butyl perbenzoate, t-butyl peroxyacetate, t-butyl peroxy-2-ethylhexanoate, t-amyl perbenzoate, t-amyl peroxyacetate, t-butyl peroxyisobutyrate, 3-hydroxy-1,1-dimethyl t-butylperoxy-2-ethylhexanoate, OO-t-amyl-O-hydrogen-monoperoxysuccinate, OO-t-butyl -O-Hydrogen-monoperoxysuccinate, di-t-butyl diperoxyphthalate, t-butylperoxy(3,3,5-trimethylhexanoate), 1,4-bis(t-butylperoxycarbo)cyclohexane, t-butylperoxy-3,5,5-trimethylhexanoate, t-butyl-peroxy-(cis-3-carboxy)propionate, allyl 3-methyl-3-t-butylperoxybutyrate, OO-t-butyl- O-isopropyl monoperoxycarbonate, OO-t-butyl-O-(2-ethylhexyl) monoperoxycarbonate, 1,1,1-tris[2-(t-butylperoxycarbonyloxy)ethoxymethyl]propane, 1,1,1-tris[2-(t-amylperoxycarbonyloxy)ethoxymethyl]propane, 1,1,1-tris[2-(cumylperoxycarbonyloxy)ethoxymethyl]propane, OO-t -amyl-O-isopropyl monoperoxycarbonate, di(4-methylbenzoyl) peroxide, di(3-methylbenzoyl) peroxide, di(2-methylbenzoyl) peroxide, didecanoyl peroxide, dilauroyl peroxide, 2,4-dibromo-benzoyl peroxide, succinic acid peroxide, dibenzoyl peroxide, di(2,4-dichloro-benzoyl) peroxide, and combinations thereof.
[0048] In one or more embodiments, the radical initiator may include an azo compound, such as azobisisobutyronitrile (AIBN), 2,2′-azobis(amidinopropyl)dihydrochloride, and the like; an azoperoxide initiator containing a mixture of a peroxide and an azodinitrile compound, such as 2,2′-azobis(2-methyl-pentanenitrile), 2,2′-azobis(2-methyl-butanenitrile), 2,2′-azobis(2-ethyl-pentanenitrile), 2-[(1-cyano-1-methylpropyl)azo]-2-methyl-pentanenitrile, 2-[(1-cyano-1-ethylpropyl)azo]-2-methyl-butanenitrile, 2-[(1-cyano-1-methylpropyl)azo]-2-ethyl, and the like.
[0049] In one or more embodiments, the radical initiator can include a carbon-carbon ("CC") free radical initiator, such as 2,3-dimethyl-2,3-diphenylbutane, 3,4-dimethyl-3,4-diphenylhexane, 3,4-diethyl-3,4-diphenylhexane, 3,4-dibenzyl-3,4 ditolylhexane, 2,7-dimethyl-4,5-diethyl-4,5-diphenyloctane, 3,4-dibenzyl-3,4-diphenylhexane, and the like.
[0050] In one or more embodiments, the hot melt adhesive composition according to the present disclosure may comprise polymers synthesized with one or more radical initiators present in a weight percent of the total polymerization mixture (wt%) ranging from a lower limit selected from one of 0.000001wt%, 0.0001wt%, 0.01wt%, 0.1wt%, 0.15wt%, 0.4wt%, 0.6wt%, 0.75wt% and 1wt% to an upper limit selected from one of 0.5wt%, 1.25wt%, 2wt%, 4wt% and 5wt%, any lower limit may be used with any upper limit. Furthermore, the concentration of the radical initiator may be envisaged to be higher or lower depending on the application of the final material.
[0051] Stabilizers The hot melt adhesive composition according to the present disclosure can include a polymer having one or more stabilizers present in a certain weight percent of the total polymerization mixture that do not interfere with polymerization in the reactor but have the ability to prevent polymerization in the monomer and comonomer feed lines.
[0052] In one or more embodiments, the stabilizer may include nitroxyl derivatives such as 2,2,6,6-tetramethyl-1-piperidinyloxy, 2,2,6,6-tetramethyl-4-hydroxy-1-piperidinyloxy, 4-oxo-2,2,6,6-tetramethyl-1-piperidinyloxy, 2,2,6,6-tetramethyl-4-amino-piperidinyloxy, and the like.
[0053] In one or more embodiments, the polymer may be formed from one or more stabilizers present in a weight percent (wt%) of the total polymerization mixture ranging from a lower limit selected from one of 0.000001 wt%, 0.0001 wt%, 0.01 wt%, 0.1 wt%, 0.15 wt%, 0.4 wt%, 0.6 wt%, 0.75 wt%, and 1 wt%, to an upper limit selected from one of 0.5 wt%, 1.25 wt%, 2 wt%, 4 wt%, and 5 wt%, any lower limit may be used with any upper limit. It is further contemplated that the concentration of the stabilizer may be increased or decreased depending on the application of the final material.
[0054] Additives The hot melt adhesive composition according to the present disclosure may also comprise fillers and additives which modify various physical and chemical properties when added to the hot melt adhesive composition and / or polymer during blending, including one or more polymer additives such as decomposition initiators, processing aids, lubricants, antistatic agents, clarifiers, nucleating agents, beta-nucleating agents, slip agents, antioxidants, anti-acid agents, light stabilizers such as HALS, IR absorbers, brighteners, organic and / or inorganic dyes, antiblock agents, processing aids, flame retardants, plasticizers, biocides, and adhesion promoters.
[0055] The hot melt adhesive compositions according to the present disclosure may comprise one or more inorganic fillers such as talc, glass fibers, marble dust, cement dust, clay, carbon black, feldspar, silica or glass, fumed silica, silicates, calcium silicate, silicate powder, glass microspheres, mica, metal oxide particles and nanoparticles such as magnesium oxide, antimony oxide, zinc oxide, inorganic salt particles and nanoparticles such as barium sulfate, wollastonite, alumina, aluminum silicate, titanium oxide, calcium carbonate, polyhedral silsesquioxanes (POSS).
[0056] In one or more embodiments, the hot melt adhesive composition according to the present disclosure may contain one or more additives and / or fillers in a weight percent (wt%) of the total composition ranging from a lower limit selected from one of 0.01 wt%, 0.02 wt%, 0.05 wt%, 1.0 wt%, 5.0 wt%, 10.0 wt%, 15.0 wt%, and 20.0 wt% to an upper limit selected from one of 25 wt%, 30 wt%, 40 wt%, 50 wt%, 60 wt%, and 70 wt%, any lower limit may be used with any upper limit.
[0057] Physical Properties of Hot Melt Adhesive Compositions In one or more embodiments, the hot melt adhesive composition may have a viscosity at 150°C according to ASTM D1084-08 ranging from a lower limit selected from any of 300 cP, 500 cP, 1000 cP, 1500 cP, 2500 cP, 3000 cP, 3500 cP, and 4000 cP to an upper limit selected from any of 4500 cP, 5000 cP, 5500 cP, 6000 cP, 7000 cP, 8000 cP, 9000 cP, 10000 cP, and 20000 cP, any lower limit may be combined with any upper limit.
[0058] In one or more embodiments, the hot melt adhesive composition may have a viscosity at 177°C according to ASTM D1084-08 ranging from a lower limit selected from any of 300 cP, 500 cP, 750 cP, 1000 cP, 1250 cP, 1500 cP, and 1750 cP to an upper limit selected from any of 2000 cP, 3000 cP, 4000 cP, 5000 cP, 6000 cP, 7000 cP, 8000 cP, 9000 cP, and 10000 cP, any lower limit may be combined with any upper limit.
[0059] In one or more embodiments, the hot melt adhesive composition may have a molten Gardner color according to ASTM D1544-04 of 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, or 7.
[0060] In one or more embodiments, the hot melt adhesive composition may have a peel adhesion fail temperature (PAFT) at 100 grams of at least 40° C., 50° C., 60° C., or 70° C. according to ASTM D4498-07, and a shear adhesion fail temperature (SAFT) at 500 grams of at least 70° C., 80° C., or 90° C. according to ASTM D4498-07.
[0061] The cloud point is the temperature at which a clear hot melt adhesive composition undergoes phase separation and forms a cloudy appearance. In one or more embodiments, the hot melt adhesive composition may have a cloud point ranging from a lower limit selected from any of 30°C, 40°C, 50°C, 60°C, 70°C, 80°C to an upper limit selected from any of 90°C, 100°C, 110°C, 120°C, 130°C, or 140°C, obtained according to ASTM D6038, any lower limit may be combined with any upper limit. In one or more embodiments, the hot melt adhesive composition does not exhibit a cloud point, thus there is no cloud point, which indicates that the components are well compatible with each other.
[0062] The thermal stability of the adhesive composition may be characterized according to test methods such as ASTM D4499. Parameters such as viscosity, viscosity change after 100 hours and 200 hours storage, and color are tested to determine thermal stability. In one or more embodiments, the hot melt adhesive composition may have a 100-hour viscosity at 177°C according to ASTM D4499 ranging from a lower limit selected from any of 300 cP, 500 cP, 750 cP, 1000 cP, 1250 cP, 1500 cP, and 1750 cP to an upper limit selected from any of 2000 cP, 3000 cP, 4000 cP, 5000 cP, 6000 cP, 7000 cP, 8000 cP, 9000 cP, and 10000 cP, any lower limit may be combined with any upper limit.
[0063] In one or more embodiments, the hot melt adhesive composition may have a 200 hour viscosity at 177°C according to ASTM D4499 ranging from a lower limit selected from any of 300 cP, 500 cP, 750 cP, 1000 cP, 1250 cP, 1500 cP, and 1750 cP to an upper limit selected from any of 2000 cP, 3000 cP, 4000 cP, 5000 cP, 6000 cP, 7000 cP, 8000 cP, 9000 cP, and 10000 cP, any lower limit may be combined with any upper limit.
[0064] In one or more embodiments, the hot melt adhesive composition may have a 100 hour viscosity change in accordance with ASTM D4499 ranging from a lower limit selected from any of 0%, 0.5%, 1%, 2%, and 3% to an upper limit selected from any of 15%, 17.5%, 20%, 25%, 30%, 40%, 50%, 60%, and 70%, any lower limit may be combined with any upper limit. In one or more embodiments, the hot melt adhesive composition may have a 200 hour viscosity change in accordance with ASTM D4499 ranging from a lower limit selected from any of 0%, 0.5%, 1%, 2%, and 3% to an upper limit selected from any of 15%, 17.5%, 20%, 25%, 30%, 40%, 50%, 60%, and 70%, any lower limit may be combined with any upper limit. The 100 hour viscosity change and 200 hour viscosity change may be either a positive or negative change, and the % viscosity change given above represents the absolute value of either the positive or negative change.
[0065] In one or more embodiments, the hot melt adhesive composition may have a 100 hour Gardner color index ranging from a lower limit selected from any of 2, 3, 4, 5, 6, 7, 8, and 8.5 to an upper limit selected from any of 9, 9.5, 10, 10.5, 11, 11.5, 12, 12.5, 13, 14, 15, 16, and 17 according to ASTM D4499 and ASTM D1544-04, any lower limit may be combined with any upper limit. In one or more embodiments, the hot melt adhesive composition may have a 200 hour Gardner color index ranging from a lower limit selected from any of 2, 3, 4, 5, 6, 7, 8, and 8.5 to an upper limit selected from any of 9, 9.5, 10, 10.5, 11, 11.5, 12, 12.5, 13, 14, 15, 16, and 17 according to ASTM D4499 and ASTM D1544-04, any lower limit may be combined with any upper limit.
[0066] In one or more embodiments, the hot melt adhesive composition may be free of edge ring after storage at 177° C. for 100 hours and / or 200 hours according to ASTM D4499.
[0067] In one or more embodiments, the hot melt adhesive composition has a mechanical strength as measured by dynamic mechanical analysis (DMA). or a glass transition temperature (T) measured by differential scanning calorimetry (DSC) ranging from an upper limit selected from any of 100°C, 90°C, and 80°C to a lower limit selected from any of -50°C, -60°C, and -70°C. g The maximum observed in the Tan δ vs. temperature plot of the hot melt adhesive composition obtained from the DMA measurement may show one, two or three maxima in the range of -70°C to 70°C, the maxima may have a lower limit selected from any of 0.05, 0.1, 0.2, 0.3, 0.4 and 0.5 to an upper limit selected from any of 1, 2, 3, 4, 5, 6, 7, 8, 9 and 10, and any lower limit may be combined with any upper limit.
[0068] Polymer Physical Properties In one or more embodiments, the hot melt adhesive composition may comprise a polymer having a melt flow rate (MFR) according to ASTM D1238 at 190°C / 2.16 kg ranging from a lower limit selected from any of 0.01 g / 10 min, 0.5 g / 10 min, 1 g / 10 min, 10 g / 10 min, 70 g / 10 min, 80 g / 10 min, 90 g / 10 min, and 100 g / 10 min to an upper limit selected from any of 140 g / 10 min, 150 g / 10 min, 160 g / 10 min, 170 g / 10 min, 200 g / 10 min, 350 g / 10 min, 450 g / 10 min, 550 g / 10 min, 1000 g / 10 min, and 2000 g / 10 min, any lower limit may be combined with any upper limit.
[0069] In one or more embodiments, the hot melt adhesive composition may comprise a polymer having a crystallinity, as measured by differential scanning calorimetry (DSC) or wide angle X-ray diffraction (WAXD) according to ASTM D3418, ranging from a lower limit selected from any of 0.1%, 1%, 10%, and 20% to an upper limit selected from any of 60%, 70%, and 80%, any lower limit may be combined with any upper limit.
[0070] In one or more embodiments, the hot melt adhesive composition has a glass transition temperature (T) ranging from an upper limit selected from any of 100° C., 90° C., and 80° C. to a lower limit selected from any of −50° C., −60° C., and −70° C., as measured by dynamic mechanical analysis (DMA) or by DSC according to ASTM D3418. g ), and any lower limit may be combined with any upper limit.
[0071] In one or more embodiments, the hot melt adhesive composition has a melting temperature (T) ranging from a lower limit selected from any of 0° C., 10° C., 20° C., 30° C., and 40° C. to an upper limit selected from any of 100° C., 110° C., 120° C., 130° C., 140° C., and 150° C., as measured by DSC according to ASTM D3418. m ), any lower limit may be combined with any upper limit. In one or more embodiments, the hot melt adhesive composition may include a polymer having a T m The polymer composition may include polymers that do not exhibit the properties of a completely amorphous polymer composition.
[0072] In one or more embodiments, the hot melt adhesive composition has a viscosity of 0° C., 5° C., 10° C., 20° C., 30° C., and 40° C., as measured by DSC in accordance with ASTM D3418, at a lower limit selected from any of 80° C., 90° C., 100° C., 120° C., 160° C., 180° C., 200° C., 220° C., 240° C., 260° C., 280° C., 290° C., 300° C., 310° C., 320° C., 330° C., 340° C., 350° C., 360° C., 370° C., 380° C., 390° C., o C, a crystallization temperature (T c), and any lower limit may be combined with any upper limit.
[0073] In one or more embodiments, the hot melt adhesive composition may comprise a polymer having a heat of crystallization in a range having a lower limit of any of 0, 10, 20, 30, 40, 50, and 60 J / g, and an upper limit of any of 140, 180, 200, 240, and 280 J / g, as measured by DSC according to ASTM D3418, any lower limit may be combined with any upper limit.
[0074] The polymerization conditions result in the production of polymers with a broad molecular weight distribution (MWD). In one or more embodiments, the hot melt adhesive composition may comprise polymers obtained within the scope of the present polymerization process with MWDs ranging from about 1 to about 60, with lower limits of any of 1, 1.5, 3, 5, or 10, and upper limits of any of 10, 20, 30, 40, 50, or 60, any lower limit may be used in combination with any upper limit. However, depending on the amount of comonomer incorporated, samples produced under high pressure conditions exhibit a broad range of MWDs from about 1 to 60. Copolymers and terpolymers produced under low pressure conditions may exhibit number average molecular weights of 1 to 300 kDa, weight average molecular weights of 1 to 1000 kDa, and MWDs of 1 to 60. Copolymers and terpolymers produced under high pressure conditions, on the other hand, may exhibit number average molecular weights of 1 to 10,000 kDa, weight average molecular weights of 1 to 20,000 kDa, and MWDs of 1 to 60.
[0075] In one or more embodiments, the hot melt adhesive composition may comprise a polymer having a hardness, as determined according to ASTM D2240, ranging from a lower limit selected from any of 25, 35, and 45 Shore A to an upper limit selected from any of 80, 90, and 100 Shore A, any lower limit may be combined with any upper limit.
[0076] In one or more embodiments, the hot melt adhesive composition may comprise a polymer having a hardness, as determined according to ASTM D2240, ranging from a lower limit selected from any of 10, 20, and 30 Shore D to an upper limit selected from any of 50, 60, and 70 Shore D, any lower limit may be combined with any upper limit.
[0077] In one or more embodiments, the hot melt adhesive composition may comprise a polymer having an elongation, tensile strength, and modulus, as determined according to ASTM D368, ranging from a lower limit selected from any of 10, 50, and 100 percent elongation to an upper limit selected from any of 500, 1000, and 2000 percent elongation; a lower limit selected from any of 1, 5, and 10 MPa tensile strength to an upper limit selected from any of 15, 30, 70, 100, and 500 MPa tensile strength; a lower limit selected from any of 0.1, 1, 5, 20, and 40 MPa modulus to an upper limit selected from any of 100, 200, 300, 1000, and 5000 MPa modulus, any lower limit may be combined with any upper limit.
[0078] In one or more embodiments, the hot melt adhesive composition has a viscosity of 0.75 g / cm according to ASTM D792. 3 , 0.85g / cm 3 , and 0.89 g / cm 3 The lower limit selected from any one of the following: 3 , 1.2g / cm 3 , 1.3g / cm 3 , and 1.5 g / cm 3 to an upper limit selected from any of the above, and any lower limit may be combined with any upper limit.
[0079] In one or more embodiments, the hot melt adhesive composition may comprise a polymer having a biobased carbon content, as determined by Method B of ASTM D6866-18, ranging from a lower limit selected from any of 1%, 5%, 10%, and 20% to an upper limit selected from any of 60%, 80%, 90%, and 100%, any lower limit may be combined with any upper limit.
[0080] In one or more embodiments, the long chain branching frequency LCBf can be calculated from GPC analysis using a GPC instrument equipped with an IR5 infrared detector and a 4 capillary viscometry detector, both from Polymer Char. Data collection was accomplished using Polymer Char software. The concentration measured by the IR5 detector was calculated considering that the full area of the chromatogram corresponds to the elution of 100% of the injected mass. The average LCBf is then calculated as follows:
[0081]
number
[0082] where R is the molar mass of the repeating unit, calculated based on the contributions of the monomer and comonomer, taking into account their respective molar percentages as determined by NMR. The calculation was performed according to M w is the mass average molecular weight, which can be calculated by universal calibration using the following equation:
[0083]
number
[0084] Calculated according to the average B n The constants are:
[0085]
number
[0086] The average g' and g constants are calculated according to the following:
[0087]
number
[0088] It is calculated according to:
[0089] ε is known as the viscosity shielding ratio and is assumed to be constant and equal to 0.7.
[0090] Intrinsic viscosity (IV 分岐 ) is the specific viscosity (η sp ) can be calculated as follows:
[0091]
number
[0092] where SA is the sample volume, KIV is the viscosity detector constant, and the volume increment (ΔV) is a constant determined by the difference between successive retention volumes (ΔV=RV i+1 -RV i ))
[0093] The intrinsic viscosity (IV 線状 ) can be calculated using the Mark-Houwink equation, while the Mark-Houwink constant is calculated from the intrinsic viscosity taking into account the concentration by the Stacey-Haney method as follows: Stacey-Haney IV (IV SH ) is based on the Stacy-Haney concentration,
[0094]
number
[0095] where C SH teeth,
[0096]
number
[0097] On the other hand, η rel is the relative viscosity (η rel = η sp +1), and (hv) i is the hydrodynamic volume at each elution volume slice from the universal calibration curve, the Mark-Houwink exponent a is defined as a reference value of 0.725 for linear polyethylene homopolymer, and the constant K is given by:
[0098]
number
[0099] It is calculated according to:
[0100]
number
[0101] From the above, the molecular weight (M SH )too,
[0102]
number
[0103] It is required according to.
[0104]
number
[0105] versus
[0106]
number
[0107] Plotting both on a logarithmic scale yields the Mark-Houwink constants k and a for linear polymers. Finally, IV 線状 is below:
[0108]
number
[0109] [In the formula, M v is the viscosity average molecular weight by concentration using the IR5 infrared detector with universal calibration, as follows:
[0110]
number
[0111] (In the formula, N i has a molecular weight of M i is the number of the i-th molecule in calculated according to It can be calculated as follows: M i is the concentration measured by the IR5 infrared detector and the hydrodynamic volume (
[0112]
number
[0113] ) is considered. i is plotted against the retention volume, the noisy extremes of the curve are removed, and then extrapolated using a third-order polynomial fit. The equation derived from this third-order polynomial fit is used to calculate M as a function of retention volume. i In one or more embodiments, the polymer may have a long chain branching frequency, as calculated by GPC analysis, in the range of 0 to 10, for example, from a lower limit of any of 1, 0.5, 1, or 1.5 to an upper limit of any of 2, 4, 6, 8, or 10, any lower limit may be combined with any upper limit.
[0114] In one or more embodiments, the polymer comprises: 13 The long chain branch content, as measured by C NMR, may be in the range of 0 to 10, for example, from a lower limit of 0, 0.2, 0.4, 0.6, 0.8, or 1 to an upper limit of 2, 4, 6, 8, or 10, and any lower limit may be combined with any upper limit.
[0115] 13 In C NMR analysis, a long chain branch (LCB) is defined as any branch with six or more carbons. 13 Based on the C NMR spectrum, the LCB content in the branched polymer (B 6+ ) is represented by the following formula: B 6+ = S 3,ポリマー - S 3,ビニルエステルモノマー (In the formula, the S3 peak is 13 (located at 32.2 ppm on the C NMR spectrum) This method calculates the branching (B 6+ ) and the chain ends of the main chain are taken into account, and the effect of long chain branches in vinyl ester monomers is 13 C NMR spectra are used to correct for the chain end effects, and the chain end effects can also be corrected for using GPC data.
[0116] In one or more embodiments, the polymer, after thermal fractionation by sequential self-nucleation and annealing (SSA), may have a heat flow versus temperature curve having a lower limit of any of 0 to 20 minima, e.g., 0, 1, 2, 3, 4, 5, 6, 7, 8, 9, or 10 minima, and an upper limit of any of 12, 14, 16, 18, or 20 minima, any lower limit may be combined with any upper limit, and the minima may be assigned to a temperature range of 140-150°C, 130-140°C, 120-130°C, 110-120°C, 100-110°C, 90-100°C, 80-90°C, 70-80°C, 60-70°C, 50-60°C, 40-50°C, 30-40°C, 20-30°C, 10-20°C, and / or 0-10°C. Such thermal fractionation can use a temperature protocol (series of heating and cooling cycles) to generate a distribution of lamellar crystals of sizes that reflect the distribution of methyl sequence lengths in the copolymers and terpolymers. Thermal fractionation can be performed under nitrogen on a TA Instruments Discovery DSC 2500. All cooling cycles can be performed at 5°C / min, and heating cycles can be performed at 20°C / min. The sample can be heated from 25°C to 150°C, held at 150°C for 5 minutes, cooled to 25°C, and held at this temperature for 3 minutes. The sample can then be heated to the first annealing temperature (140°C), held at this temperature for 5 minutes, and cooled to 25°C. The sample can then be heated again to the next annealing temperature (130°C), held at this temperature for 5 minutes, and cooled to 25°C. This procedure can be repeated in 10°C increments until the final annealing temperature (such as, but not limited to, 0°C) is reached. The sample can then be heated to 150° C. at 20° C. / min to obtain a melting profile.
[0117] In one or more embodiments, the polymer may have a thermal stability, as measured by thermogravimetric analysis (TGA), such that the ratio of mass loss to total comonomer content between 250° C. and 400° C. ranges from a lower limit of 0 to 2, e.g., 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, and 1, to an upper limit of 1.2, 1.4, 1.6, 1.8, or 2, any lower limit combined with any upper limit.
[0118] In one or more embodiments, the polymer may have a storage modulus at 0° C. of 0.1 MPa to 10 GPa, for example, a lower limit of any of 0.1, 1, 2, 5, 10, 20, 40, 60, 80, or 100 MPa and an upper limit of any of 200 MPa, 300 MPa, 400 MPa, 500 MPa, 700 MPa, 1 GPa, 5 GPa, or 10 GPa, any lower limit in combination with any upper limit.
[0119] In one or more embodiments, the polymer may have one or two relaxation maxima between −75° C. and 75° C. in a plot of tan δ versus temperature, with the higher temperature peak designated α and the lower temperature peak designated β. α (the temperature corresponding to the α peak) may vary between −75° C. and 75° C., for example, between any lower limit of −75, −60, −50, −40, −30, −20, −10, or 0° C., and any upper limit of 10, 20, 30, 40, 50, 60, or 75° C., any lower limit may be combined with any upper limit. β (The temperature corresponding to the β peak) may vary between -75°C and 50°C, for example between any lower limit of -75, -60, -50, -40, -30, -20, -10, or 0°C, and any upper limit of 10, 20, 30, 40, or 50°C, and any lower limit may be combined with any upper limit.
[0120] Method for preparing hot melt adhesive composition The hot melt adhesive composition according to the present disclosure can be prepared in any conventional batch, semi-batch or continuous mixing equipment. In one or more embodiments, the hot melt adhesive composition can be prepared by mixing, which may include melt mixing, in any known process for adhesive formulation, such as sigma mixers, horizontal mixers, kneaders, blenders, Banbury mixers, mixing rollers, extruders, and any other available manufacturing equipment.
[0121] In one or more embodiments, all of the components may be mixed together in a single step. In other embodiments, if multiple polymers are present in the hot melt adhesive composition, there may be a premixing step of the polymers in conventional mixing equipment, for example in an extruder, or alternatively pelletized, before mixing with the other components in a subsequent mixing step.
[0122] In one or more embodiments, the hot melt adhesive composition may be mixed at a temperature ranging from a lower limit selected from any of 100°C, 110°C, 120°C, 130°C, 140°C, and 150°C to an upper limit selected from any of 180°C, 190°C, 200°C, 210°C, and 220°C, any lower limit may be combined with any upper limit.
[0123] Polymer Preparation Method In one or more embodiments, the polymer in the hot melt adhesive composition according to the present disclosure may be prepared in a reactor by polymerization of ethylene and one or more branched vinyl ester monomers. The method of reacting the comonomer in the presence of a radical initiator may include any suitable method in the art, including liquid phase polymerization, pressure radical polymerization, bulk polymerization, emulsion polymerization, and suspension polymerization. In one or more embodiments, the reactor may be a batch or continuous reactor at a pressure less than 500 bar, known as a low pressure polymerization system. In one or more embodiments, the reaction is carried out in a low pressure polymerization process in which ethylene and one or more vinyl ester monomers are polymerized in the liquid phase of an inert solvent and / or one or more liquid monomers. In one embodiment, the polymerization comprises an amount of initiator for free radical polymerization of about 0.0001 to about 0.01 millimoles, calculated as the total amount of initiator for free radical polymerization per liter of volume of the polymerization zone. The amount of ethylene in the polymerization zone depends primarily on the total reactor pressure, which may range from about 20 bar to about 500 bar, and the temperature, which may range from about 20° C. to about 300° C. In one or more embodiments, the pressure in the reactor may have a lower limit of any of 20, 30, 40, 50, 75, or 100 bar, and an upper limit of any of 100, 150, 200, 250, 300, 350, 400, 450, or 500 bar, and the temperature in the reactor may have a lower limit of any of 20° C., 50° C., 75° C., or 100° C., and an upper limit of any of 150° C., 200° C., 250° C., or 300° C. The liquid phase of the polymerization process according to the present disclosure may include ethylene, one or more vinyl ester monomers, an initiator for free radical polymerization, and may optionally include one or more inert solvents, such as tetrahydrofuran (THF), chloroform, dichloromethane (DCM), dimethylsulfoxide (DMSO), dimethylcarbonate (DMC), hexane, cyclohexane, ethyl acetate (EtOAc), acetonitrile, toluene, xylene, ether, dioxane, dimethyl-formamide (DMF), benzene, or acetone.Copolymers and terpolymers produced under low pressure conditions can exhibit number average molecular weights of 1-300 kDa, weight average molecular weights of 1-1000 kDa, and MWDs of 1-60.
[0124] In one or more embodiments, the comonomer and one or more free radical polymerization initiators are polymerized in a continuous or batch process at temperatures above 50° C. and pressures above 1000 bar, known as high pressure polymerization systems. For example, pressures above 1000, 1100, 1200, 1500, 1600, 1700, 1800, 1900, 2000, 2100, 2200, 2300, 2400, 2500, 3000, 5000, or 10000 bar may be used. Copolymers and terpolymers produced under high pressure conditions may have a number average molecular weight (Mn) of 1 to 10000 kDa and a weight average molecular weight (Mw) of 1 to 20000 kDa. The molecular weight distribution (MWD) is obtained from the ratio of the weight average molecular weight (Mw) and the number average molecular weight (Mn) obtained by GPC. Copolymers and terpolymers produced under high pressure conditions can have MWDs of 1-60.
[0125] In one or more embodiments, conversion during polymerization in low pressure and high pressure polymerization systems is defined as the mass or mass flow rate of polymer produced divided by the mass or mass flow rate of monomer and comonomer and may have a lower limit of any of 0.01%, 0.1%, 1%, 2%, 5%, 7%, 10% and an upper limit of any of 15%, 17%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 60%, 70%, 80%, 90%, 99% or 100%.
[0126] multilayer structure The hot melt adhesive compositions according to the present disclosure may be used to create multi-layer structures or articles by bonding similar or dissimilar substrates. Although there is no practical limit to the type of substrates that may be bonded using the hot melt adhesive compositions according to the present disclosure, exemplary substrates may include textiles, non-woven materials, polymers and polymeric materials such as polyurethane, ethylene vinyl acetate copolymer (EVA), polypropylene, polyethylene, polyvinyl chloride, polyester, polyamide, polyolefin, polyacrylic, polystyrene, metal, cellulose, such as wood, cardboard, paper, kraft paper, etc. The substrates may take the form of films, blocks, sheets, fibers, threads, strips, ribbons, coatings, foils, bands, etc.
[0127] In one or more embodiments, a method of bonding a substrate to a similar or dissimilar substrate may include applying a hot melt adhesive composition to at least one substrate and bonding the layers together. For example, the adhesive composition may be melted and applied to at least one substrate to which it is to be bonded. Application onto the substrate may be, for example, by use of a calendar, a laminating machine (e.g., a flat-bed laminating machine), by various welding techniques, or by various batch processes that may use various heat sources.
[0128] One or more embodiments of the present disclosure are also directed to multi-layer articles, which may include at least one layer of the hot melt adhesive composition and one or more substrate layers. The substrate layers of the multi-layer articles may be made from woven fabrics, non-woven materials, polymers and polymeric materials such as polyurethane, ethylene vinyl acetate copolymer (EVA), polypropylene, polyethylene, polyvinyl chloride, polyester, polyamide, polyolefin, polyacrylic, polystyrene, metal, cellulose, such as wood, cardboard, paper, kraft paper, and the like.
[0129] In one or more embodiments, a multi-layer article according to the present disclosure may include a hot melt adhesive composition having a bio-based carbon content for bonding one or more substrate layers together. In one or more embodiments, a method of bonding substrates to similar or dissimilar substrates may include applying a hot melt adhesive composition having a bio-based carbon content to at least one substrate and bonding the layers together. EXAMPLES
[0130] The following examples are merely illustrative and should not be construed as limiting the scope of the present disclosure: Ethylene-based polymers incorporating various amounts of vinyl acetate and HEXION™ vinyl carbonyl monomer VeoVa™ 10 (a mixture of isomeric vinyl esters of versatic acid having 10 carbon atoms) were produced under high pressure conditions, and the resulting compositions were analyzed for several polymer properties.
[0131] Ethylene, VeoVa™ 10 (Hexion), tert-butyl peroxy-2-ethylhexanoate, heptane (99%, Sigma Aldrich), and vinyl acetate (99%, Sigma Aldrich) were used as received. The synthesis of copolymers and terpolymers of VeoVa™ 10 and optionally vinyl acetate with ethylene was carried out under high pressure conditions.
[0132] Example 1 The polymer compositions were prepared using continuous free radical polymerization of the comonomer mixture by mixing various flow rates of ethylene, vinyl acetate, VeoVa™ 10, heptane, and tert-butyl peroxy-2-ethylhexanoate in a high pressure reactor. Before each polymerization, the reactor was purged five times with 2200-2300 bar of ethylene. Each reaction was initiated by heating the reactor to 200° C. and feeding ethylene to a pressure of 1900-2000 bar. A continuous flow of ethylene was then fed to the reactor at a rate of 2000 g / h. After the target pressure and a stable ethylene flow were achieved, the comonomer was added to the reactor. A mixture of initiator and heptane was introduced to the system at a flow rate of 2 mL / h. The reaction mixture was recovered and the reactor was washed with xylene at 145° C. The resulting polymer was dissolved in xylene and precipitated in cold methanol, then vacuum filtered. The resulting polymer contained 77.6 wt% ethylene and 22.4 wt% VeoVa™ 10.
[0133] Example 2 A polymer composition was prepared as described in Example 1, except that the comonomer mixture in the sequential polymerization was varied. The resulting polymer contained 70.4 wt% ethylene, 21.2 wt% vinyl acetate, and 8.4 wt% VeoVa™ 10.
[0134] Example 3 A polymer composition was prepared as described in Example 1, except that the comonomer mixture for the sequential polymerization was varied. The resulting polymer contained 69.2 wt% ethylene, 25.8 wt% vinyl acetate, and 5 wt% VeoVa™ 10.
[0135] Comparative Example 1 Comparative Example 1 is a commercial resin HM2528 manufactured by Braskem, which is a copolymer of ethylene vinyl acetate (EVA) with high vinyl acetate content for specially formulated applications and hot melt adhesives. The resin exhibits low viscosity and excellent compatibility with adhesive resins and waxes. In addition, it delivers excellent loading properties with any type of filler. This polymer contains 72 wt% ethylene and 28 wt% vinyl acetate.
[0136] Comparative Example 2 Comparative Example 2 is a commercial resin, HM150, manufactured by Braskem, which is a copolymer of ethylene vinyl acetate (EVA) designed for a variety of hot melt applications. The resin combines moderately low viscosity with excellent adhesion. HM150 is highly compatible with most tackifying resins and waxes. The polymer contains 80 wt% ethylene and 20 wt% vinyl acetate.
[0137] Comparative Example 3 Comparative Example 3 is a blend of the samples used in Comparative Example 1 and Comparative Example 2. The components of the blend were mixed in composition (19.6 wt% of Comparative Example 1 and 80.4 wt% of Comparative Example 2) to obtain a blend with a melt flow index of 115 g / 10 min at 190° C. / 2.16 kg.
[0138] Table 1 summarizes the chemical composition and melt flow rate for all synthetic copolymers and terpolymers. MFR was determined at 190°C / 2.16kg according to ASTM D1238.
[0139] [Table 1]
[0140] Preparation of Hot Melt Adhesive Compositions
[0141] Example 4 A hot melt adhesive composition was prepared by adding 66 g of the polymer composition obtained in Example 1, 85.4 g of Escorez™ 5637 tackifier, 44 g of Sasol™ H1 wax and 0.6 g of Irganox™ 1010 antioxidant to a metal container and storing in an oven at 177° C. for 1 hour. The molten ingredients were then transferred to a mixer and mixed at 177° C. for 15 minutes.
[0142] Example 5 A hot melt adhesive composition was prepared as described in Example 4, except that the polymer composition obtained in Example 1 was replaced with the polymer composition obtained in Example 2.
[0143] Example 6 A hot melt adhesive composition was prepared as described in Example 4, except that the polymer composition obtained in Example 1 was replaced with the polymer composition obtained in Example 3.
[0144] Comparative Example 4 A hot melt adhesive composition was prepared as described in Example 4, except that the polymer composition obtained in Example 1 was replaced with the polymer composition of Comparative Example 1.
[0145] Comparative Example 5 A hot melt adhesive composition was prepared as described in Example 4, except that the polymer composition obtained in Example 1 was replaced with the polymer composition of Comparative Example 2.
[0146] Comparative Example 6 A hot melt adhesive composition was prepared as described in Example 4, except that the polymer composition obtained in Example 1 was replaced with the polymer composition obtained in Comparative Example 3.
[0147] Table 2 shows the wt% ratio of each component used to produce the hot melt adhesive compositions of Examples 4-6 and Comparative Examples 4-6. As illustrated in Table 2, the amounts of all components were kept consistent, and only the types of commercially available synthetic copolymers and terpolymers were varied. The formulations shown in Table 2 are standard formulations for packaged type hot melt adhesives.
[0148] [Table 2]
[0149] Table 3 summarizes the properties of various hot melt adhesive compositions. The viscosities of Examples 4-6 and Comparative Examples 4-6 at 150°C and 177°C were determined according to ASTM D1084-08. The results show that the hot melt adhesive compositions of Examples 4-6, which contain a copolymer of ethylene and a branched vinyl ester monomer, or a terpolymer of ethylene, vinyl acetate and a branched vinyl ester monomer, have a lower viscosity than the hot melt adhesive composition of Comparative Examples 4-6, which does not contain a branched vinyl ester monomer.
[0150] The molten Gardner color of Examples 4-6 and Comparative Examples 4-6 was determined according to ASTM 1544-04, and the peel adhesion failure temperature (PAFT) and shear adhesion failure temperature (SAFT) were determined according to ASTM D4498-07.
[0151] The cloud points of Comparative Examples 4-6 were determined according to ASTM D6038. Cloud point is the temperature at which a clear solution undergoes phase separation and forms a hazy appearance. As shown in Table 3, Comparative Examples 4-6 exhibited cloud points of 107°C, 101°C, and 104°C.
[0152] The thermal stability of the hot melt adhesive compositions of Examples 4-6 and Comparative Examples 4-6 was determined by measuring the 100-hour viscosity, 100-hour color, and percent viscosity change according to ASTM D4499. Parameters such as viscosity, viscosity change, and color after 100 hours storage are tested to determine the thermal stability.
[0153] [Table 3]
[0154] (Examples 7-11) Examples 7-11 are exemplary terpolymers of one or more embodiments produced in an industrial plant that normally produces EVA copolymers. The resulting EVA containing 28 wt% VA was transferred to the terpolymer by adjusting reactor parameters to gradually replace the vinyl acetate feed stream with VeoVa 10™ until the desired comonomer ratio was obtained. Table 4 shows the general reactor conditions for the production of the aforementioned terpolymers.
[0155] [Table 4]
[0156] Comparative Example 7 Comparative Example 7 is a commercial resin HM728 manufactured by Braskem, which is a copolymer of ethylene and vinyl acetate (EVA) with a high vinyl acetate content for special compounding applications and hot melt adhesives. The resin exhibits high viscosity and excellent compatibility with adhesive resins and waxes. In addition, the resin achieves excellent loading properties with any type of filler. The polymer contains 72 wt% ethylene and 28 wt% vinyl acetate.
[0157] Table 5 summarizes the chemical composition and melt flow rate for all synthetic copolymers and terpolymers. MFR was determined at 190°C / 2.16kg according to ASTM D1238.
[0158] [Table 5]
[0159] Preparation of Hot Melt Adhesive Compositions
[0160] Example 12 A hot melt adhesive composition was prepared by adding 100 g of the polymer composition obtained in Example 7, 218 g of Escorez™ 5637 tackifier, 80 g of Sasol™ H1 wax, and 2 g of Irganox™ 1010 antioxidant to a metal container and storing in an oven at 177° C. for 1 hour. The molten ingredients were then transferred to a mixer and mixed at 177° C. for 15 minutes.
[0161] Example 13 A hot melt adhesive composition was prepared as described in Example 12, except that the polymer composition obtained in Example 7 was replaced with the polymer composition obtained in Example 8.
[0162] Example 14 A hot melt adhesive composition was prepared as described in Example 12, except that the polymer composition obtained in Example 7 was replaced with the polymer composition obtained in Example 9.
[0163] Example 15 A hot melt adhesive composition was prepared as described in Example 12, except that the polymer composition from Example 7 was replaced with the polymer composition from Example 10.
[0164] (Example 16) A hot melt adhesive composition was prepared as described in Example 12, except that the polymer composition from Example 7 was replaced with the polymer composition from Example 11.
[0165] Comparative Example 8 A hot melt adhesive composition was prepared as described in Example 12, except that the polymer composition obtained in Example 7 was replaced with the polymer composition obtained in Comparative Example 7.
[0166] Table 6 shows the wt% ratio of each component used to prepare the hot melt adhesive compositions of Examples 12-16 and Comparative Example 8. As shown in Table 6, the amounts of all components were kept consistent, only the type of terpolymer was changed. The formulations shown in Table 6 are standard formulations for structural adhesive applications.
[0167] [Table 6]
[0168] Table 7 summarizes the properties of various hot melt adhesive compositions. The viscosities of Examples 12-16 and Comparative Example 8 were determined according to ASTM D1084-08 at 150°C and 177°C. The results show that the hot melt adhesive compositions of Examples 12-16, which include a terpolymer of ethylene, vinyl acetate, and a branched vinyl ester monomer, have lower viscosities than the hot melt adhesive composition of Comparative Example 8, which does not include a branched vinyl ester monomer.
[0169] The molten Gardner color of Examples 12-16 and Comparative Example 8 was determined according to ASTM 1544-04, and the peel adhesion failure temperature (PAFT) and shear adhesion failure temperature (SAFT) were determined according to ASTM D4498-07.
[0170] The cloud points of Examples 12-16 and Comparative Example 8 were determined according to ASTM D6038. The cloud point is the temperature at which a clear solution undergoes phase separation and forms a hazy appearance. As shown in Table 7, Examples 12-16 exhibited cloud points in the range of 89°C to 95°C.
[0171] The thermal stability of the hot melt adhesive compositions of Examples 12-16 and Comparative Example 8 was determined by measuring the 200 hour viscosity, 200 hour color, and percent viscosity change according to ASTM D4499. Parameters such as viscosity, viscosity change, and color after 200 hours storage are tested to determine the thermal stability.
[0172] [Table 7]
[0173] Preparation of Hot Melt Adhesive Compositions
[0174] (Example 17) A hot melt adhesive composition was prepared by adding 100 g of the polymer composition obtained in Example 7, 218 g of Westrez™ 5101 tackifier, 80 g of Sasol™ H1 wax, and 2 g of Irganox™ 1010 antioxidant to a metal container and storing in an oven at 177° C. for 1 hour. The molten ingredients were then transferred to a mixer and mixed at 177° C. for 15 minutes.
[0175] (Example 18) A hot melt adhesive composition was prepared as described in Example 17, except that the polymer composition obtained in Example 7 was replaced with the polymer composition obtained in Example 8.
[0176] (Example 19) A hot melt adhesive composition was prepared as described in Example 17, except that the polymer composition obtained in Example 7 was replaced with the polymer composition obtained in Example 9.
[0177] (Example 20) A hot melt adhesive composition was prepared as described in Example 17, except that the polymer composition from Example 7 was substituted for the polymer composition from Example 10.
[0178] Example 21 A hot melt adhesive composition was prepared as described in Example 17, except that the polymer composition from Example 7 was substituted for the polymer composition from Example 11.
[0179] Comparative Example 9 A hot melt adhesive composition was prepared as described in Comparative Example 17, except that the polymer composition obtained in Example 7 was replaced with the polymer composition obtained in Comparative Example 7.
[0180] Table 6 shows the wt% ratio of each component used to prepare the hot melt adhesive compositions of Examples 17-21 and Comparative Example 9. The amounts of all components were kept consistent, only the type of terpolymer was changed, as shown in Table 8. The formulations shown in Table 6 are standard formulations for structural adhesive applications.
[0181] [Table 8]
[0182] Table 9 summarizes the properties of various hot melt adhesive compositions. The viscosities of Examples 17-21 and Comparative Example 9 were determined according to ASTM D1084-08 at 150°C and 177°C. The results show that the hot melt adhesive compositions of Examples 17-21, which contain a terpolymer of ethylene, vinyl acetate, and a branched vinyl ester monomer, have a lower viscosity than the hot melt adhesive composition of Comparative Example 9, which does not contain a branched vinyl ester monomer.
[0183] The molten Gardner color of Examples 17-21 and Comparative Example 9 was determined according to ASTM 1544-04, and the peel adhesion failure temperature (PAFT) and shear adhesion failure temperature (SAFT) were determined according to ASTM D4498-07.
[0184] The cloud points of Examples 17-21 and Comparative Example 9 were determined according to ASTM D6038. As shown in Table 7, Examples 17-21 exhibited cloud points in the range of 89°C to 95°C.
[0185] The thermal stability of the hot melt adhesive compositions of Examples 17-21 and Comparative Example 9 was determined by measuring the 200-hour viscosity, 200-hour color, and percent viscosity change according to ASTM D4499. Parameters such as viscosity, viscosity change, and color after 200 hours of storage were obtained to determine the thermal stability.
[0186] [Table 9]
[0187] Although only a few exemplary embodiments have been described in detail above, those skilled in the art will readily appreciate that many modifications are possible in the exemplary embodiments without substantially departing from the present invention. Accordingly, all such modifications are intended to be included within the scope of the present disclosure, as defined in the following claims. In the claims, the means-plus-function clauses are intended to cover the structures described herein as performing the recited function, and equivalent structures as well as structural equivalents. Thus, while nails and screws may not be structural equivalents in that nails utilize cylindrical surfaces to fasten wooden parts while screws utilize helical surfaces, in the context of fastening wooden parts, nails and screws may be equivalent structures. It is the express intent of the applicants not to invoke 35 U.S.C. § 112(f) to any limitation of any claim herein, except where the claim expressly uses the words "means for" with the relevant function.
Claims
1. Ethylene, one or more branched vinyl ester monomers; With vinyl acetate which may be optionally included and Tackifier 1. A hot melt adhesive composition comprising:
2. The polymer is obtained by GPC. a number average molecular weight in the range of 5 to 10,000 kDa, and Molecular weight distribution in the range of 1 to 60 2. The hot melt adhesive composition of claim 1, having
3. 10. The hot melt adhesive composition of claim 1, further comprising a wax and / or an antioxidant.
4. The one or more branched vinyl ester monomers have the general structure (I) or the general structure (II): 【Chemistry 1】 (wherein R 1 , R 2 and R 3 have a total carbon number of 3 to 20), 【Chemistry 2】 (wherein R 4 and R 5 have a total carbon number of 7).
2. The hot melt adhesive composition of claim 1, having
5. The polymer is a copolymer of ethylene and one or more branched vinyl esters, or 2. The hot melt adhesive composition of claim 1, wherein the polymer is a terpolymer of ethylene, one or more branched vinyl esters, and vinyl acetate.
6. The polymer, an ethylene content ranging from 10 to 99.99 wt%; and A branched vinyl ester content ranging from 0.01 to 90 wt %, having 10. The hot melt adhesive composition of claim 1, optionally having a vinyl acetate content in the range of 0.01 to 89.99 wt.%.
7. The hot melt adhesive composition of claim 1, wherein the polymer is polymerized under conditions comprising a reactor pressure of greater than 1000 bar and a reactor temperature of greater than 50°C.
8. The hot melt adhesive composition of claim 1, further comprising a secondary polymer in an amount ranging from 0.1 to 90 wt % of the hot melt adhesive composition.
9. The hot melt adhesive composition of claim 1, wherein the secondary polymer is selected from the group consisting of EVA, ethylene-acrylic ester copolymers, polyethylene, polypropylene, styrene block copolymers, and combinations thereof.
10. In accordance with ASTM D3418, a melting temperature of the polymer in the range of 0 to 150°C, and / or the crystallization temperature of the polymer in the range of 0 to 150° C., and / or 10. The hot melt adhesive composition of claim 1 having a heat of crystallization of the polymer in the range of 0 to 280 J / g.
11. The hot melt adhesive composition of claim 1, wherein the polymer has a storage modulus in the range of 0.1 MPa to 10 GPa at 0°C.
12. The hot melt adhesive composition of claim 1, wherein the melt flow rate (MFR) of the polymer at 190°C / 2.16 kg according to ASTM D1238 ranges from 0.01 g / 10 min to 1000 g / 10 min.
13. The hot melt adhesive composition of claim 1, wherein the density of the polymer according to ASTM D792 ranges from 0.85 g / cm 3 to 1.5 g / cm 3 .
14. The hot melt adhesive composition of claim 1, wherein the bio-based carbon content of the polymer according to ASTM D6866-18 ranges from 1% to 100%.
15. The method of claim 1, wherein the polymer is present in an amount ranging from 10 wt % to 90 wt % of the hot melt adhesive composition; 10. The hot melt adhesive composition of claim 1, wherein the tackifier is present in an amount ranging from 10 wt% to 90 wt% of the hot melt adhesive composition.
16. The hot melt adhesive composition of claim 1, having a viscosity at 150° C. in accordance with ASTM D1084-08 in the range of 300 cP to 20,000 cP.
17. The hot melt adhesive composition of claim 1, having a viscosity at 177°C according to ASTM D1084-08 in the range of 300 cP to 10,000 cP.
18. The hot melt adhesive composition of claim 1, having a molten Gardner color in the range of 1 to 7 according to ASTM D1544-04.
19. The composition of claim 1, further comprising a peel adhesion failure temperature (PAFT) at 100 grams according to ASTM D4498-07 of at least 40°C; 2. The hot melt adhesive composition of claim 1, having a shear adhesion failure temperature (SAFT) at 500 grams according to ASTM D4498-07 of at least 70°C.
20. The hot melt adhesive composition of claim 1, having a cloud point according to ASTM D6038 in the range of 30° C. to 140° C. or absent.
21. In accordance with ASTM D4499, and / or a 100 hour viscosity at 177°C in the range of 300 cP to 10,000 cP; 100 hour color value is in the range of 3 to 17; and / or 2. The hot melt adhesive composition of claim 1, wherein the absolute value of the 100 hour percent viscosity change is in the range of 0% to 70%.
22. In accordance with ASTM D4499, and / or a viscosity at 177°C for 200 hours in the range of 300 cP to 10,000 cP; 200 hour color value is in the range of 3 to 17; and / or 2. The hot melt adhesive composition of claim 1, wherein the absolute value of the 200 hour percent viscosity change is in the range of 0% to 70%.
23. A method for producing a hot melt adhesive composition, comprising: adding a polymer formed from ethylene, one or more branched vinyl ester monomers, and optionally vinyl acetate, and a tackifier into a mixer; adding optional waxes and / or antioxidants into the mixer; mixing the polymer and tackifier, and optionally a wax and / or an antioxidant, at a temperature in the range of 110° C. to 220° C. to form a hot melt adhesive composition; A method comprising:
24. A method for joining a substrate to a similar or dissimilar substrate, comprising the steps of: applying to at least one substrate a hot melt adhesive composition according to claim 1; bonding together at least one substrate and a hot melt adhesive composition; A method comprising:
25. A method for producing a coating composition comprising: at least one layer of the hot melt adhesive composition of claim 1; One or more substrate layers; A multi-layer article comprising: